Intestinal tolerability of nitroxybutyl-flurbiprofen in rats. Issue 5 (May 1997) - Somasundaram, S; Rafi, S; Jacob, M; Sigthorsson, G; Mahmud, T; Sherwood, R; Price, A B; Macpherson, A; Scott, D; Wrigglesworth, J M; Bjarnason, I
Abstract : BACKGROUND: Nitric oxide derivatives of non-steroidal anti-inflammatory drugs (NSAIDs) are thought to be much less ulcerogenic than their parent compounds. AIM: To compare the effect and potency of flurbiprofen and nitroxybutyl-flurbiprofen to uncouple mitochondrial oxidative phosphorylation (an early pathogenic event in NSAID enteropathy), increase intestinal permeability (transitional stage), and cause macroscopic small intestinal damage. METHODS: In vitro uncoupling potency was assessed using isolated coupled rat liver mitochondria and in vivo by electron microscopy of rat small intestinal mucosa (two hours after the drugs). A dose-response study with flurbiprofen (single doses of 5, 10, 20, and 40 mg/kg) and equimolar doses of nitroxybutyl-flurbiprofen was performed; assessing their effect on intestinal permeability (at 18-20 hours), with 51Cr EDTA, and the number of pointed (< 5 mm) and longitudinal (> 5 mm) small intestinal ulcers at 24 hours. RESULTS: Flurbiprofen, but not nitroxybutyl-flurbiprofen, stimulated coupled respiration in vitro. Both drugs, however, uncoupled in vivo; in the case of nitroxybutyl-flurbiprofen possibly because hydrolysis of its ester bond released free flurbiprofen. Intestinal permeability was uniformly and equally increased with both drugs compared with controls. The number of small intestinal ulcers, pointed and longitudinal, was significantly reduced with nitroxybutyl-flurbiprofen apart from the number of longitudinal ulcers with the highest dose. CONCLUSIONS: These studies show that nitroxybutyl-flurbiprofen is associated with significantly less macroscopic damage in the small intestine than flurbiprofen but was associated with mitochondrial damage in vivo and caused similar increases in permeability of the small intestine, suggesting that its beneficial effect is on the later pathogenic stages of the damage.